Wines without Latitude: Global and local forces and the geography of the Thai wine industry - Glenn Banks; Ratchaphong Klinsrisuk; Sittipong Dilokwanich; Polly Stupples (EchoGéo)
Wine grape production has historically been restricted to temperate latitudes – largely between 30 and 50 degrees above and below the equator. Recently, though, wine has started to be made in countries within tropical regions. This paper explores the development and features of the Thai wine industry, the largest of the SE Asian wine producers. Linking in to arguments concerning economic and cultural globalisation, the paper explores the motivations and origins of the Thai producers, the environmental constraints and local adaptations to these, the regulatory and cultural constraints to the development of the industry, its global connections and prospects for the industry. Our argument is that despite its small size, the Thai wine industry neatly encapsulates many of the complexities around globalisation, demonstrating the fusion of global cultural trends, nationalistic economic growth, the increasingly global character of wine industry participants, and the continuing constraints on all these global processes of domestic political and regulatory regimes.